PERJUANGAN PEREMPUAN MELAWAN HEGEMONI PATRIARKI (Kajian terhadap Novel Perempuan Berkalung Sorban Karya Abidah El-Khalieqy) - Mohammad Muzakka (KAJIAN SASTRA, 2010)
Woman Struggling to reach patriarchal hegemony does not happen in reality but it is happened in Indonesian literatures. One of them is Perempuan Berkalung Sorban, a novel written by Abidah El Khalieqy. The general aim of the research was described how a woman struggles patriarchal hegemony in novel. The result of research shows that Anisa, as the main character in novel, struggles to reach patriarchal hegemony in the community of a moslem boarding school (pesantren) community that place women inferiority.